Navigating Sharia Business Regulation in the Era of Sustainable Development: A Maqashid al-Shariah and SDGs-Based Approach - Nahdhah, Nahdhah; Megasari, Indah Dewi; Hidayatullah, Rahmad Ade (Sharia Faculty Islamic Economic Law Study Department, 2026)
The growing global concern for sustainable development has prompted a major transformation in legal systems and financial regulation, including the Islamic banking sector. Conceptually, maqashid al-shariah and the Sustainable Development Goals (SDGs) share a normative orientation toward promoting public welfare, social justice, and sustainable development. Despite this philosophical convergence, the integration of these two frameworks into Indonesia’s Islamic banking regulatory system continues to face significant normative challenges. The existing legal framework remains predominantly focused on formalistic sharia compliance and the prudential principle, whereas the sustainability dimension has not yet been comprehensively operationalized within Islamic banking regulation. This study aims to analyse the normative gaps in Islamic banking regulation that impede the integration of maqashid al-shariah and the SDGs, while formulating a legal reform model capable of addressing such obstacles. This research adopts a normative legal method, or doctrinal legal research, using statutory, conceptual, and philosophical approaches. It examines several principal regulatory frameworks, including Law Number 6 of 2023 on Job Creation, Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector, sustainable finance regulations, sources of Islamic law, and contemporary legal doctrine. The data are analysed through a normative gap analysis model supported by systematic, teleological, and maqashid-based legal interpretation. The findings indicate that the barriers to integration arise not only from normative deficiencies, but also from regulatory fragmentation, institutional design, and a legal culture that continues to prioritize a formalistic fiqh-based compliance approach. Through the lens of Law and Development Theory, this study argues that Indonesia’s legal structure remains in a transitional phase and does not yet fully support the operational integration of maqashid al-shariah and sustainability principles. Accordingly, this study proposes a legal-operational framework based on maqashid compliance indicators as an adaptive model of legal reform to strengthen the integration of Islamic ethical values and sustainability principles within Islamic banking regulation.